Azo Crosslinkers, Synthesis and Their Reduction - LASHANIZADEGAN, ASGHAR; SOOZANDEHFAR, HASHEM (Asian Journal of Chemistry, 2010)
Polymers containing azo crosslinks have been used as coating devices and protect the drug in a solid dosage form. They are reduced by colonic bacteria which allow drug release within the colon. This study was concerned with the investigation of the mechanism of release by bacterial reduction of azo crosslinkers. Chain-growth copolymers containing hydrophilic and hydrophobic monomers and a bifunctional azo aromatic crosslinker were prepared and their reduction in bacterial cultures was investigated. The polymers swelled and their dry weight decreased on incubation in aqueous media. The amount of weight loss increased with increasing proportion of the hydrophilic monomer. There was no enhancement of weight reduction in bacterial cultures which had demonstrable azo reduction activity, suggesting that cleavage of azo bonds in the polymer network did not take place.